Review of Investigations on Hazard Chains Triggered by River-Blocking Debris Flows and Dam-Break Floods - Chen, Huayong; Ruan, Hechun; Chen, Jiangang; Li, Xiao; Yu, Yunhan (Frontiers in Earth Science, 2022)
The Tibetan Plateau suffers from various types of geohazards (collapses, landslides, and debris flows.) due to abrupt changes in complex topography and weather conditions. Global warming and frequent high-intensity earthquakes in recent years have exacerbated the situation. Collapses and landslides provide vast amount of soil and debris which are conveyed downstream by runoff caused by extreme rainfalls to form large-scale debris flows; then, the debris flows block rivers and finally form dam-break floods, that is, a hazard chain triggered by debris flows. Along the evolution direction of the hazard chain, the affected areas are constantly amplified. This study first summarizes the related research studies on river blockage, debris-flow dam failure, and the hazard chain triggered by debris flows and then points out the drawbacks of existing research studies. Overall, the research (including mechanism, risk assessment, key prevention, and control technologies) on the hazard chain triggered by debris flows is still in its infancy and is disconnected among single hazard types in the hazard chain; meanwhile, the understanding of the mechanism of debris flow blocking the river is not enough; the established model and discriminant have minimal application scope, and there is no empirical model and dynamic model of debris-flow dam failure. Finally, several key scientific issues of this field were raised: 1) it is necessary to elaborate the coupling mechanism of debris-flow dam formation and construct the discriminant and numerical model of debris flow blocking the river with high precision and a wide application range. 2) It is necessary to further study the failure mechanism of a debris-flow dam, construct the numerical model of the failure process of a debris-flow dam, and accurately simulate the outburst flood hydrograph. 3) It is necessary to clarify the critical transformation conditions and dynamic evolution process of the hazard chain caused by debris flows, complete the accurate quantitative simulation of the whole disaster chain process, then establish a complete risk assessment system of the hazard chain, and finally develop some key prevention and control technologies suitable for the hazard chain.